ChemInform Abstract: Catalytic 1, 4‐Selective Hydrosilylation of Pyridines and Benzannulated Congeners. Issue 8 (25th February 2014) - Koenigs, C. David F.; Klare, Hendrik F. T.; Oestreich, Martin
Abstract This reaction likely proceeds via an ionic one‐step hydride transfer distinguishing it from previously reported methods with radical mechanisms.